Imaging Pituitary Vasopressin 1B Receptor in Humans with the PET Radiotracer 11C-TASP699 - Naganawa, Mika; Nabulsi, Nabeel B; Matuskey, David; Henry, Shannan; Ropchan, Jim; Lin, Shu-Fei; Gao, Hong; Pracitto, Richard; Labaree, David; Zhang, Ming-Rong; Suhara, Tetsuya; Nishino, Izumi; et al. (The Journal of nuclear medicine (1978), 2022)
Arginine vasopressin is a hormone that is synthesized mainly in the hypothalamus and stored in the posterior pituitary. Receptors for vasopressin are categorized into at least 3 subtypes (V1A, V1B, and V2). Among these subtypes, the V1B receptor (V1BR), highly expressed in the pituitary, is a primary regulator of hypothalamic-pituitary-adrenal axis activity and thus a potential target for treatment of neuropsychiatric disorders such as depression and anxiety. N-tert-butyl-2-[2-(6-methoxypyridine-2-yl)-6-[3-(morpholin-4-yl)propoxy]-4-oxopyrido[2,3-d]pyrimidin-3(4H)-yl]acetamide (TASP699) is a novel PET radiotracer with high affinity and selectivity for V1BR. The purpose of this study was to characterize the pharmacokinetic and binding profiles of 11C-TASP699 in humans and determine its utility in an occupancy study of a novel V1BR antagonist, TS-121. Methods: Six healthy subjects were scanned twice with 11C-TASP699 to determine the most appropriate kinetic model for analysis of imaging data and test–retest reproducibility of outcome measures. Nine healthy subjects were scanned before and after administration of TS-121 (active component: THY1773) to assess V1BR occupancy. Metabolite-corrected arterial input functions were obtained. Pituitary time–activity curves were analyzed with 1- and 2-tissue-compartment (1TC and 2TC, respectively) models and multilinear analysis 1 (MA1) to calculate distribution volume (VT). Relative test–retest variability (TRV) and absolute TRV were calculated. Since no brain region could be used as a reference region, percentage change in VT after TS-121 administration was computed to assess its receptor occupancy and correlate with plasma concentrations of the drug. Results: 11C-TASP699 showed high uptake in the pituitary and no uptake in any brain region. The 2TC model provided better fits than the 1TC model. Because the MA1 VT estimates were similar to the 2TC VT estimates, MA1 was the model of choice. The TRV of VT was good (TRV, −2% ± 14%; absolute TRV, 11%). THY1773 reduced VT in a dose-dependent fashion, with a half-maximal inhibitory concentration of 177 ± 52 ng/mL in plasma concentration. There were no adverse events resulting in discontinuation from the study. Conclusion: 11C-TASP699 was shown to display appropriate kinetics in humans, with substantial specific binding and good reproducibility of VT. Therefore, this tracer is suitable for measurement of V1BR in the human pituitary and the V1BR occupancy of TS-121, a novel V1BR antagonist.